Flow cytometry-based study of model marine microalgal consortia revealed an ecological advantage of siderophore utilization by the dinoflagellate Amphidinium carterae - Malych, Ronald; Stopka, Pavel; Mach, Jan; Kotabová, Eva; Prášil, Ondřej; Sutak, Robert (Computational and structural biotechnology journal, 2022)
Investigations of phytoplankton responses to iron stress in seawater are complicated by the fact that iron concentrations do not necessarily reflect bioavailability. Most studies to date have been based on single species or field samples and are problematic to interpret. Here, we report results from an experimental cocultivation model system that enabled us to evaluate interspecific competition as a function of iron content and form, and to study the effect of nutritional conditions on the proteomic profiles of individual species. Our study revealed that the dinoflagellate Amphidinium carterae was able to utilize iron from a hydroxamate siderophore, a strategy that could provide an ecological advantage in environments where siderophores present an important source of iron. Additionally, proteomic analysis allowed us to identify a potential candidate protein involved in iron acquisition from hydroxamate siderophores, a strategy that is largely unknown in eukaryotic phytoplankton.
Keywords: AUC, area under curve; PsaD, photosystem I reaction center subunit II; NPQ, nonphotochemical quenching; FBP1, putative ferrichrome-binding protein; RR, long-term iron sufficiency; PsbC, photosystem II CP43 reaction center protein; FACS, fluorescence-activated cell sorting; NBD, nitrobenz-2-oxa-1,3-diazole; AtpE, ATP synthase; Amphidinium carterae; PetA, cytochrome b6/f; Marine microalgae; FBAI, fructose-bisphosphate aldolase I; (s)PLS-DA, (sparse) partial least squares discriminant analysis; PsaC, photosystem I iron-sulfur center; PAGE, polyacrylamide gel electrophoresis; PsaE, photosystem I reaction center subunit IV; DFOB, desferrioxamine B; SOD1, superoxide dismutase [Cu-Zn]; PSI, photosystem I; PSII, photosystem II; BCS, bathocuproinedisulfonic acid disodium salt; LHCX, light-harvesting complex subunits; CREG1, cellular repressor of E1A stimulated genes 1; Iron; ISIP, iron starvation induced protein; EDTA, ethylenediaminetetraacetic acid; LL, long-term iron limitation; ENT, enterobactin; PsaL, photosystem I reaction center subunit XI; Flow cytometry; LR, iron enrichment; Siderophores; Proteomics; FOB, ferrioxamine B; PsbV, cytochrome c-550; FBAII, fructose-bisphosphate aldolase II